1993
DOI: 10.1029/93gl02490
|View full text |Cite
|
Sign up to set email alerts
|

A new interpretation on the origin of enhanced ion acoustic fluctuations in the upper ionosphere

Abstract: Enhanced ion acoustic fluctuations have been recently observed by incoherent scatter radars in the upper ionosphere. Here it is suggested that these fluctuations can be due to the Langmuir wave decay L→L’+S. In this process the “pump” Langmuir waves (L) are produced by a beam instability due to streaming soft electrons. Those waves then produce backscattered Langmuir waves (L’) and ion acoustic waves (S). Estimations of the required electron beam energy and flux, as well as the beam number density are given. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 21 publications
2
65
0
Order By: Relevance
“…Muschietti et al (1994), Newman et al (1994) and Forme (1993). The beam parameters we have used are well within the limits given by these authors.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Muschietti et al (1994), Newman et al (1994) and Forme (1993). The beam parameters we have used are well within the limits given by these authors.…”
Section: Discussionmentioning
confidence: 62%
“…The ®rst formulation of this model by Forme (1993) was not able to explain some of the observed spectral signature like simultaneously propagating ion-acoustic waves in parallel and antiparallel (with respect to the magnetic ®eld) direction. This study shows that the parametric decay of beam generated Langmuir waves can lead to up-going and down-going ion-acoustic waves, propagating separately or simultaneously.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…St.-Maurice et al [ 1996] discuss the inferred field-aligned currents in terms of intense parallel electric fields of up to a few hundred microvolts per meter in magnitude together with horizontal scales of a few hundred meters or less. Forme [1993] has suggested that ion-acoustic fluctuations may be due to parametric decay of Langmuir waves, and Wahlund et al [1992a] propose a theory based on ion-ion two-stream instabilities. Foster et al [1988] using the Millstone Hill 440-MHz radar at angles of at least 11 ø away from the local magnetic field direction revealed echoes that could easily have been mistaken for satellite passes had they not had a consistent altitude profile and come from a fixed region of space.…”
mentioning
confidence: 99%